Housing Wealth Effects: Evidence from an Australian Panel - Windsor, Callan; Finlay, Richard; Jääskelä, Jarkko (My University, 2015)
We explore the positive relationship between house prices and household spending by following a panel of Australian households. No evidence for ‘traditional housing wealth effects' is found, with young homeowners exhibiting the largest wealth effects. Young renters also exhibit a positive consumption response to house prices, although less so than young homeowners. This suggests that increasing house prices raise spending via easing credit constraints and a common association between house prices and a third factor. Results from a cohort-level panel are similar to those using household-level data, suggesting that ‘pseudo-panels' may be used as a partial substitute for actual panels.
Economica
Keywords: Income & Finance -- Financial Management (inc Budgeting); Families -- Households; Income & Finance -- Wealth; Families and relationships; Income, wealth and finances; Families; Income & Finance; Wealth; Households; Financial Management (inc Budgeting); Families and relationships; Income, wealth and finances